2021
DOI: 10.1159/000520218
|View full text |Cite
|
Sign up to set email alerts
|

Improved Prognostic Precision in Uveal Melanoma through a Combined Score of Clinical Stage and Molecular Prognostication

Abstract: Introduction: Prognosis of uveal melanoma (UM) is assessed using clinical staging or molecular testing. Two modalities often used for prognostication are the American Joint Committee on Cancer (AJCC) staging and a tumor gene expression profile (GEP), the outcomes of which are often discordant. This paper discusses a Total Risk Score created to combine the discordant information from both sources. Methods: A retrospective case series was conducted of all patients presenting with UM over six years to two referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Based on the TNM classification by AJCC, most of our cases were diagnosed at Stage IIB, followed by Stage IIIA, which may explain the relatively lower survival rates. Moreover, in accordance with previously published papers [ 41 , 42 ], we confirmed that older age and stage III were independent prognostic factors in our cohort of patients.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the TNM classification by AJCC, most of our cases were diagnosed at Stage IIB, followed by Stage IIIA, which may explain the relatively lower survival rates. Moreover, in accordance with previously published papers [ 41 , 42 ], we confirmed that older age and stage III were independent prognostic factors in our cohort of patients.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have attempted to combine AJCC staging and GEP and have created a total risk score that seems to provide an accurate prognosis for uveal melanoma. 61 Another study combined AJCC staging with chromosome 3 and 8q status and found this to provide more of an accurate prognostication of uveal melanoma. This study found that a normal genetic status of chromosomes 3 and 8 minimized the prognostic effect of AJCC staging.…”
Section: Uveal Melanomamentioning
confidence: 99%
“…Currently, UM prognostication for metastatic potential relies on clinical information (i.e., the tumor size and location/extension), and when available, the tumor biopsy-based molecular information (i.e., from gene expression, chromosomal aberration, or gene mutation analysis) and/or histopathological information depending on obtainable tumor material (in vivo by fine-needle aspiration biopsy from the eyes undergoing eye-preserving therapy or ex vivo from the enucleated eyes). While the primary tumor biopsy-based molecular information has been shown to significantly improve UM prognostication [11][12][13][14][15][16], the liquid biopsy-based approaches (molecular analyses of body fluids), which are increasingly used in other cancers, have also increasingly become a focus of UM studies in recent years [2,17]. Liquid biopsy constitutes not only a less invasive alternative (to direct tumor biopsy) but also provides additional advantages such as repeat testing (to monitor therapy response, local recurrence, and metastatic potential) and the ability to capture the heterogeneous nature of cancer [2,18].…”
Section: Introductionmentioning
confidence: 99%